Trauma, pamięć, afekt: echa terroru w powieści graficznej Сурвило Olgi Ławrientiewej - Pawletko, Beata (Studia Rossica Posnaniensia, 2022)
The article analyzes Olga Lavrenteva’s graphic novel Survilo, which echoes the terror, especially the Stalinist repression and the blockade of Leningrad. Lavrenteva is a graphic artist, author of comic books, representative of the third generation, who presents the story of her grandmother, Valentina Survilo, and her relatives in an unconventional form. Translated into the language of comic books, this family story focuses on the fate of many inhabitants of the Soviet Union. At the same time, as if on the sidelines, Lavrenteva raises an important issue – the coexistence of memory and affect, which is the result of long-term silence. Survilo is not only a record of the past but also of the emotional states of her grandmother, the paralyzing fear that accompanied her, i.e. the physical and psychological costs that the survivors had to bear. Lavrenteva’s graphic novel successfully fits into the new practices of commemoration and witnessing, which are still a novelty in Russia, carrying a great potential for critical revision of the dark past, and – above all – for building a community of memory based on the foundations of intergenerational dialogue.